Pengaruh Art Therapy untuk Menurunkan Stres Akademik pada Mahasiswa - Weny Nurrohmah Utami; Meilla Dwi Nurmala; Arga Satrio Prabowo (Guidance : Jurnal Bimbingan dan Konseling, 2023)
This study aims to examine the effect of art therapy techniques carried out through individual counseling services to reduce academic stress on guidance and counseling students at FKIP Untirta Batch 2020. This study used an experimental research method. The experimental design used was Single Subject Research (SSR) with an A-B-A design. The research subject was one student who experienced academic stress. The data obtained were analyzed using descriptive statistics, then displayed in the form of tables and graphs. The results showed that the average percentage at baseline 1 was 74% with 100% stability, in the intervention conditions it obtained an average percentage of 37.8% with 33.3% stability and in baseline 2 conditions an average of 36% with 100% stability. The data shows a decrease of 36% from baseline 1 to baseline 2 with a data overlap of 0% which indicates that providing interventions with art therapy techniques can have a good effect on reducing academic stress.